Work Transformation of Generation Y in the Current of Information Technology - Asmiatiningsih, Sri; Hwihanus, Hwihanus; Riyadi, Slamet (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The research aims to examine the concrete impact of work transformation triggered by information technology on Generation Y in the current industrial environment. This study will employ a quantitative approach with quantitative methods to collect data. The research population consists of Generation Y employees in both private and government institutions exposed to the use of information technology in their work context. Sampling will be randomly conducted on a number of Generation Y employees representing various work units in several manufacturing companies and government agencies in the West Nusa Tenggara Province. This study uses a survey instrument developed based on existing theoretical frameworks and relevant literature. Descriptive statistical analysis will be used to provide an overview of the respondents' profiles and main patterns in the data. The collected data will be processed and analyzed using the Statistical Package for the Social Sciences (SPSS) software version 26. Linear regression analysis and descriptive statistical analysis will be employed to explain the relationship between technology adaptation variables and work engagement, organizational commitment, and turnover intention. Simultaneous analysis results indicate that the four variables, namely Information Technology Adaptation (X1), Price and Organizational Commitment (X2), Organizational Support (X3), and Work Engagement (X4), collectively have a significant influence on Turnover Intention (Y). In this regard, the findings suggest that to reduce the tendency of job turnover intention, organizations need to simultaneously pay attention to and enhance these factors. Efforts to improve the level of technology adaptation, price and organizational commitment, organizational support, and employee work engagement can help reduce the level of turnover intention. Turnover intention is not only influenced by one factor but is the result of various interrelated factors. Managing technology adaptation, organizational commitment, organizational support, and work engagement is crucial in minimizing the tendency to intend to leave the job.